2021
DOI: 10.3390/su13031357
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Financing Strategy in a Capital-Constrained Supply Chain with Retailer Green Marketing Efforts

Abstract: The purpose of this research is to examine the green supply chain (GSC) financing decisions of manufacturers and capital-constrained retailers in order to establish a Stackelberg game model under decentralized and centralized decision-making. This paper studies the influence of retailers’ choice of trade credit or bank loan financing strategy on a GSC’s performance and analyzes their decision-making tendency. The results show that manufacturers should provide trade credit and participate in retailers’ financin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 55 publications
(72 reference statements)
0
9
1
Order By: Relevance
“…Leading retailers should take effective measures to promote green marketing among firms and to increase the market demand for low-carbon products, thereby forming a virtuous low-carbon circular economy. This conclusion differs from the optimal decision of the manufacturer-led green supply chain in that the wholesale price is impacted by green sensitivity [22,59,68].…”
Section: Property3 the Influence Of Green Sensitivity On Firm Decision-makingcontrasting
confidence: 57%
“…Leading retailers should take effective measures to promote green marketing among firms and to increase the market demand for low-carbon products, thereby forming a virtuous low-carbon circular economy. This conclusion differs from the optimal decision of the manufacturer-led green supply chain in that the wholesale price is impacted by green sensitivity [22,59,68].…”
Section: Property3 the Influence Of Green Sensitivity On Firm Decision-makingcontrasting
confidence: 57%
“…Retailers’ access to green finance means that retailer has enough funds available to take the necessary steps to produce, sell, and promote green products (Zhang et al 2021 ). To undertake green marketing or distribution of green products, it is vital that financing is available for retailers.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Hua et al [8] analyzed the financing and ordering strategies of the retailer under option contracts, and found that the retailer always tends to raise capital from the supplier. Cao et al [27] and Zou et al [28] examined the influence of low-carbon production on supply chain financing decisions and found that the manufacturer's low-carbon production will not affect enterprises' financing decisions. Zhang et al [29], Zhang et al [30], and Yang et al [31] studied the financing strategy selection of a single-channel supply chain and found that trade credit leads to financing equilibrium under certain conditions.…”
Section: Supply Chain Financingmentioning
confidence: 99%